2010
DOI: 10.1007/s00701-010-0648-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the European Working Time Directive in neurosurgery reduces continuity of care and training opportunities

Abstract: The EWTD has had a marked adverse impact on continuity of care for neurosurgical patients at St. George's Hospital. Residents' training opportunities were reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Numerous European studies have demonstrated reduced continuity of care, involvement in patient care directly with faculty, exposure to high-quality operative education, and general discontent among faculty and trainees. [28][29][30][31][32][33][34] The experiential learning model has been used to formulate medical educator professional development curricula 35 and could similarly be used to refine surgical educational curricula. The pre- (Table 5) [36][37][38][39][40] ; generally, our results confirm these findings on a larger scale and for the first time compare surgical faculty with residents and students.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous European studies have demonstrated reduced continuity of care, involvement in patient care directly with faculty, exposure to high-quality operative education, and general discontent among faculty and trainees. [28][29][30][31][32][33][34] The experiential learning model has been used to formulate medical educator professional development curricula 35 and could similarly be used to refine surgical educational curricula. The pre- (Table 5) [36][37][38][39][40] ; generally, our results confirm these findings on a larger scale and for the first time compare surgical faculty with residents and students.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand a guideline is only a guide or suggestion, but once published it can assume an authority on evidence, which is often lacking. Indeed in some cases it is argued that strict adherence to a guideline can be counterproductive [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to reduced training opportunities [1][2][3][4] and as a consequence there has been a drive to maximise such opportunities, both within working hours and through the use of adjuncts such as educational courses.…”
Section: Neurosurgical Trainees' Perceptions Of Course Value and Studmentioning
confidence: 99%